The Effect of Local Taxes and Retribution on Economic Growth in Indonesia - Wicaksono, Bayu Rhamadani (Universitas Muhammadiyah Magelang, 2020)
The purpose of the study is to analyze the effect of local taxes and retributions on the economic growth in Indonesia. The data used are secondary data from provinces in Indonesia 2014-2017 using panel data regression with Random Effects Model (REM). The results are as follows, first, the local taxes has a negative and significant impact on the economic growth in Indonesia. Second, the retributions have a positive and significant effect on the economic growth in Indonesia. The government should evaluate and plan a good strategy for the next period so that the potential revenues of local taxes and retributions can increase economic growth gradually.